UVB irradiation as a tool to assess ROS‐induced damage in human spermatozoa. (9th July 2013) - Amaral, S.; Redmann, K.; Sanchez, V.; Mallidis, C.; Ramalho‐Santos, J.; Schlatt, S.
Summary: One of the consequences of oxygen metabolism is the production of reactive oxygen species (ROS) which in a situation of imbalance with antioxidants can damage several biomolecules, compromise cell function and even lead to cellular death. The particularities of the sperm cell make it particularly vulnerable to ROS attack compromising its functionality, mirrored in terms of fertility outcome and making the study of the origin of sperm ROS, as well as the alterations they cause very important. In the present work, we used UVB irradiation, an easy experimental approach known as a potent inducer of ROS formation, to better understand the origin of ROS damage without any confounding effects that usually exist in disease models in which ROS are reported to play a role. To address these issues we evaluated sperm mitochondrial ROS production using the Mitosox Red Probe, mitochondrial membrane potential using the JC‐1 probe, lipid peroxidation through BODIPY probe and vitality using PI. We observed that UVB irradiation leads to an increase in sperm mitochondrial ROS production and lipid peroxidation that occur previously to an observable mitochondrial dysfunction. We concluded that sperm UVB irradiation appears to be a good and easily manipulated in vitro model system to study mitochondria‐induced oxidative stress in spermatozoa and its consequences, which may be relevant in terms of dissecting the action pathways of many other pathologies, drugs and contaminants, including endocrine disruptors.